MicroRNA-101-3p reverses gemcitabine resistance by inhibition of ribonucleotide reductase M1 in pancreatic cancer. Issue 1 (1st April 2016) - Fan, Pei; Liu, Li; Yin, Yefeng; Zhao, Zhefu; Zhang, Yiyao; Amponsah, Prince S.; Xiao, Xi; Bauer, Nathalie; Abukiwan, Alia; Nwaeburu, Clifford C.; Gladkich, Jury; Gao, Chao; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDA) is among the most lethal malignancies and resistance to chemotherapy prevents the therapeutic outcome. MicroRNAs provide a novel therapeutic strategy. Here, the established and primary human PDA cell lines PANC-1, AsPC-1, MIA-PaCa2, AsanPaCa, BxPC-3 and three gemcitabine-resistant subclones were examined. A gene expression profiling revealed that the ribonucleotide reductase M1 (RRM1) was upregulated in gemcitabine-resistant cells, which was confirmed by qRT-PCR, Western blot analysis and immunostaining. Inhibition of RRM1 by lipotransfection of siRNA reduced its expression and reversed gemcitabine resistance. The expression of RRM1 correlated to gemcitabine resistance in vitro and was higher in malignant patient pancreas tissue compared to non-malignant pancreas tissue. By microRNA expression profiling, we identified microRNA-101-3p as top-downregulated candidate. Lipotransfection of microRNA-101-3p mimics inhibited the expression of RRM1, reduced the luciferase activity of its 3'UTR and sensitized for gemcitabine-induced cytotoxicity. These results underline the relevance of microRNA-101-3p-driven regulation of RRM1 in drug resistance and suggest the co-delivery of microRNA-101-3p and gemcitabine for more effective therapy outcome.